Refugee Resettlement, Redistribution and Growth - Leonid V. Azarnert (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper studies the effect of refugee resettlement on human capital accumulation. The analysis is performed in a growth model with endogenous fertility. I show how refugee resettlement from a more advanced and wealthier economy to a less advanced and less wealthy economy combined with income transfers is Pareto-improving for indigenous populations in both countries. I also derive conditions for the proposed resettlement policy to stimulate human capital accumulation and hence economic growth in both economies.
Keywords: D30; F22; J10; O10; 330; refugee resettlement; fertility; human capital; growth